Hoppla! based on two choreographies: Quatuor no. 4 (1986, danced by Johanne Saulnier and Jean-Luc Ducourt ; music played by Walter Hus and Stefan Poelmans) ; Mikrokosmos (1987, danced by Anne Teresa de Keersmaeker, Nadine Ganase, Roxane Huilmand and Fumiyo Ikeda ; music played by the Mondriaan Kwartet) - Bartók, Béla 1881-1945 (Éditions à Voir, 2007)
Videodance work comprising two choreographic pieces to music by Bartók